Outcomes and Complications of the Midline Anterior Approach 3 Years after Lumbar Spine Surgery - Fischer, Charla R. (Adv Orthop, 2014)
Objective. The purpose of this study was to evaluate a new questionnaire to assess outcomes related to the midline anterior lumbar approach and to identify risk factors for negative patient responses. Methods. A retrospective review of 58 patients who underwent anterior lumbar surgery at a single institution for either degenerative disc disease or spondylolisthesis in 2009 was performed. The outcome measures included our newly developed Anterior Lumbar Surgery Questionnaire (ALSQ), ODI, and EQ-5D. Results. There were 58 patients available for followup, 27 women and 31 men. The average age at surgery was 50.8 years, with an average followup of 2.92 years. The average change in ODI was 34.94 (22.7) and EQ-5D was 0.28 (0.29). The rate of complications with the anterior approach was 10.3% and there was one male patient (3.2%) with retrograde ejaculation. Determination of the effectiveness of the new ALSQ revealed that it significantly correlated to the EQ-5D and ODI (P < 0.05). Smoking was associated with a negative response on thirteen questions. BMP use was not associated with a negative response on any sexual function questions. Conclusions. Our new Anterior Lumbar Surgery Questionnaire determines patient perceived complications related to the midline anterior lumbar surgical approach.